Using immobilization as a quick diagnostic indicator for resistance to phosphine. (June 2019) - Athanassiou, Christos G.; Kavallieratos, Nickolas G.; Brabec, Daniel L.; Agrafioti, Paraskevi; Sakka, Maria; Campbell, James F.
Abstract: In the present study, we evaluated a quick diagnostic test for resistance to phosphine in stored-product beetle species. We collected different populations of thirteen species, obtained from different laboratories in different counties, i.e., USA, Greece, Australia, Germany and Spain. There were also tested populations that have been sampled from different facilities (field populations). We used the Detia Degesch Phosphine Tolerance Test Kit (DDPTTK), which is based on the exposure of the insects on a high concentration of phosphine for shorter exposure periods. The tested concentrations to phosphine were 1000 and 3000 ppm. Briefly, 20 adults of the tested populations were placed in a 100 ml plastic syringe. The observations were taken every 2 min and the exposed adults were classified as either walking normally or being immobilized (knocked down), i.e., not walking normally. In light of our findings, the time to reach knockdown of all adults was notably reduced at 3000 ppm in comparison with 1000 ppm. For the majority of the species and laboratory populations tested, at 3000 ppm, the time required for knockdown ranged between 8 and 14 min. In contrast, for some of the field populations, knockdown did not reach 100% even after 300 min of exposure, at either 1000 or 3000 ppm. Based on the results of the present study, we recommend that the DDPTTK can be operated at 3000 ppm, and we provide the critical threshold times per species for the characterization of tolerance/resistance. Highlights: A quick diagnostic test for resistance of insects to phosphine was evaluated. For laboratory populations, diagnosis required 8–14 min at 3000 ppm. For some field populations, immobilization was not 100% after 300 min at 3000 ppm. The quick test can be utilized by the industry during fumigations on site.